2022
DOI: 10.3390/diagnostics12030702
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Liver Steatosis Using Controlled Attenuation Parameter among Patients with Chronic Hepatitis C Infection Treated with Direct-Acting Antivirals Therapy Who Achieved Sustained Virological Response

Abstract: Chronic hepatitis C virus (HCV) infection induces hepatic steatosis due to viral and host factors. However, information regarding the effects of direct-acting antivirals (DAAs) therapy on liver steatosis and fibrosis is limited. Vibration-controlled transient elastography (VCTE) with a controlled attenuation parameter (CAP) represents a non-invasive method, which has been used in the last few years for the detection of hepatic steatosis and fibrosis before and at a sustained virological response at 12 weeks (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…The resolution of hepatic inflammation and the reversal of fibrosis are also likely contributing factors to the decrease in liver stiffness that occurs after viral eradication [ 32 ]. The results of our study suggest that mean LSM values had decreased after DAAs regimens, with an increasing CAP score, similar to another study of ours, which has been published recently [ 33 ]. Moreover, the high value of the CAP score at SVR post-evaluation is correlated with increasing BMI, WC, triglycerides, and total cholesterol levels.…”
Section: Discussionsupporting
confidence: 92%
“…The resolution of hepatic inflammation and the reversal of fibrosis are also likely contributing factors to the decrease in liver stiffness that occurs after viral eradication [ 32 ]. The results of our study suggest that mean LSM values had decreased after DAAs regimens, with an increasing CAP score, similar to another study of ours, which has been published recently [ 33 ]. Moreover, the high value of the CAP score at SVR post-evaluation is correlated with increasing BMI, WC, triglycerides, and total cholesterol levels.…”
Section: Discussionsupporting
confidence: 92%
“…Reports on the effect of DAA treatment on blood TGs are, however, contradictory. An increase in blood TGs was described in some studies [19][20][21], whereas other studies could not identify a change in TG levels by DAA therapy [3,22,23] or even observed a decline [24,25]. It was also reported that elimination of HCV led to a rise in serum TGs in HCV patients with fibrosis stages F0-F2 but not in those with advanced disease [21,26].…”
Section: Introductionmentioning
confidence: 99%
“…В научной литературе данные о динамике стеатоза печени после достижения УВО противоречивы. Часть из них демонстрирует уменьшение САР ТМ по данным ТФ, в том числе и у пациентов с ЦП, через 12-24 недели после окончания терапии ПППД [32][33][34][35], другие, наоборот, прогрессию стеатоза печени [36][37][38]. В проведенном исследовании зарегистрирована высокая распространенность стеатоза печени как до начала ПВТ, так и при длительном мониторинге после достижения УВО.…”
Section: Discussionunclassified